How to align social and productive investments to accelerate growth - Badiane, Ousmane (2009)
Ousmane Badiane, Lead Specialist,Food and Agricultural Policy, Africa Region, World Bank 14th May 2008, Royal museum for Central Africa in Tervuren, Belgium